"To Live" Beyond Good and Evil. Issue 1 (1st March 2001) - Wang, Rujie
I believe that for a long time now Chinese films have been too abstract, conceptual, gimmicky. They don't relate at all to the lives of ordinary Chinese people. I'm certain that most audiences will like this film. We haven't gone overboard on the tragic elements, but rather have focused on the minute, amusing details in the life of a nobody. There are tears and laughter, one following the other in a gentle rhythm like the breath of a bellows. Zhang Yimou